2018
DOI: 10.20944/preprints201810.0166.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Fat Mass and Obesity Associated (FTO) Gene and Hepatic Glucose and Lipid Metabolism

Abstract: Common genetic variants of the fat mass and obesity associated (FTO) gene are strongly associated with obesity and type 2 diabetes. FTO is ubiquitously expressed, but appears to have tissue-specific roles. Earlier studies have focused on the role of hypothlamic FTO in the regulation of metabolism. However, it appears that FTO plays a role in the regulation of metabolism in a tissue-specific manner. Recent studies suggest that expression of hepatic FTO is regulated by metabolic signals such as nutrients and hor… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 45 publications
2
23
0
Order By: Relevance
“…Finally, we can claim that the effect size of A-allele on HDL-c and leptin is approximately close to the effect size in the European population; thus, we can conclude that the associations and effect size of this variant in this population is similar to those in Europeans, since our population is Caucasians as Europeans [16,27]. Evidences showed that this gene can regulate lipid profile through hepatic signalling pathways; however, the exact mechanism is not yet understood [34,35] Since HDL-c level is strongly associated with noncommunicating diseases, based on these findings, carriers of A-allele might be more susceptible to metabolic disturbances and subsequently affected by non-communicating diseases such as metabolic syndrome, cardiovascular diseases and other chronic diseases in comparison to noncarriers. In addition, the associations of this variant are different across various regions, ethnicities, and age groups.…”
Section: Discussionsupporting
confidence: 63%
“…Finally, we can claim that the effect size of A-allele on HDL-c and leptin is approximately close to the effect size in the European population; thus, we can conclude that the associations and effect size of this variant in this population is similar to those in Europeans, since our population is Caucasians as Europeans [16,27]. Evidences showed that this gene can regulate lipid profile through hepatic signalling pathways; however, the exact mechanism is not yet understood [34,35] Since HDL-c level is strongly associated with noncommunicating diseases, based on these findings, carriers of A-allele might be more susceptible to metabolic disturbances and subsequently affected by non-communicating diseases such as metabolic syndrome, cardiovascular diseases and other chronic diseases in comparison to noncarriers. In addition, the associations of this variant are different across various regions, ethnicities, and age groups.…”
Section: Discussionsupporting
confidence: 63%
“…A well‐known feature of metabolic syndrome is increase of lipid accumulation in the trunk region, which causes excessive visceral fat deposition (Mizuno, ). In order to confirm that the rising body weight gain was truly an increase of fat mass, we isolated the epididymal white adipose tissue from the mice.…”
Section: Resultsmentioning
confidence: 99%
“…FTO polymorphisms are associated with high BMI and insulin resistance and may contribute to the development of NAFLD. Upregulation of FTO is consistently observed in clinical NAFLD patients as well as in rodent models, suggesting the potential implication of FTO in NAFLD [55,56].…”
Section: M6a In Liver Diseasesmentioning
confidence: 98%